(untitled) (SCIÉNDO INGENIUM, 2022)
The Strategic Planning of Comprehensive Control, seeks to insert a control measure through the Balanced Scorecard, with this it is intended to solve the main problems that afflict the III Departmental Command of La Libertad of the Volunteer Fire Department of Peru, which is an organization without fines profit, which has different decentralized bodies. In order to determine the effect of Strategic Planning in achieving the objectives of the Departmental Command, the following steps are intended to be followed; Analysis and diagnosis of the current situation, Determination of the SWOT Strategic Matrix, Strategic Deployment of the Action Plans. The method that will be used in the research will have a non-experimental descriptive design, since the behavior of the variables will be observed over time and a proposal will be made for their improvement. Based on the results obtained, the diagnosis of the current situation was previously carried out. It is concluded that in the strategic diagnosis, the tools used give a quantitative result that allows a preliminary conclusion of how the organization is, on the other hand, the objectives determined 32 projects to be carried out.